Chronic low-grade inflammation as a key mechanism in the development of civilization diseases - a narrative review - Kubuj-Pawliszyn, Malwina; Gąsior, Natalia; Dryżałowski, Piotr; Cymer, Emil; Anasiewicz, Michał (Journal of Education, Health and Sport, 2026)
Background Chronic low-grade inflammation (CLGI) is a persistent activation of the immune system that typically does not produce any signs of acute inflammation, chronically affects metabolism, endothelial function, and homeostasis. Contemporary evidence suggests that CLGI constitutes a biological “common background” for many civilization diseases including visceral obesity and insulin resistance, type 2 diabetes, atherosclerosis and cardiovascular diseases, metabolically associated steatotic liver disease as well as selected neuropsychiatric and neurodegenerative disorders, cancers, and chronic respiratory and kidney diseases. This mechanism is further amplified by immune ageing (inflammaging) which may help explain the increasing burden of multimorbidity in the population. Aim The aim of this article is to present CLGI as a pathogenetic mechanism in the development of civilization diseases and to discuss: (1) the main axes (immunometabolism, the gut–microbiota–barrier axis, endothelial dysfunction, oxidative stress, and ageing-related processes), (2) clinically useful biomarkers, and (3) the prevention and treatment. Material and methods A narrative review of the literature was conducted. The scope included publications addressing CLGI and its associations with selected civilization diseases. Searches were performed in databases e.g., PubMed/MEDLINE using keywords such as including, among others, “low-grade inflammation”, “metainflammation/metaflammation”, “inflammaging”, “hs-CRP”, “NLRP3”, “gut microbiota”, “atherosclerosis”, “MASLD/NAFLD”, “CKD inflammation”, and “COPD systemic inflammation”. The selection was purposive and problem-oriented: meta-analyses, systematic reviews, large cohort studies, and randomized clinical trials were prioritized and findings were synthesized thematically (mechanisms → biomarkers → disease entities → modulation strategies). Results The literature synthesis indicates that CLGI is sustained by the overlap of metabolic and environmental stimuli. Key contributors include dysfunction of visceral adipose tissue, disturbances of the intestinal axis (dysbiosis, increased intestinal barrier permeability), persistent activation of innate immunity (including inflammasome pathways) and endothelial and microcirculatory dysfunction. Biomarkers such as hs-CRP are clinically practical. However, the interpretation requires consideration of confounders (infections, comorbidity burden, obesity, and exacerbations of chronic diseases). CLGI supports the development and progression of metabolic disorders, atherosclerosis, metabolically driven liver disease, selected brain–immune axis disorders, and it increases the risk of complications and multimorbidity in CKD and COPD. Conclusions CLGI constitutes a coherent, biologically plausible mechanism linking lifestyle factors and ageing to the development of civilization diseases. Clinically, strategies that reduce the stimuli driving CLGI such as reduction of visceral obesity, physical activity, dietary modification, sleep improvement and stress reduction and the identification of individuals with an elevated inflammatory-risk phenotype are of particular importance. In selected populations, interventions with documented anti-inflammatory effects may be considered as an adjunct to standard management.